Hafnium isotopes in Arctic Ocean water - Zimmermann, B; Porcelli, D; Frank, M; Andersson, P; Baskaran, M; Lee, D; Halliday, A (Elsevier, 2009)
The first isotopic compositions of dissolved hafnium in seawater from across the Arctic Ocean are reported. Most samples from the four sub-basins of the Arctic Ocean have values within error of an average of εHf = + 0.8. Combined Hf-Nd isotope compositions do not fall on the well-established positive correlation for mantle and crustal rocks. Instead, Arctic waters have Hf that is more radiogenic than that typically found in rocks with similar Nd isotope compositions, a feaure previously found in ferromanganese crusts and waters from the Pacific Ocean. Arctic seawater samples generally fall on the lower part of the ferrogmanganese crust array, reflecting influences of inputs from Arctic rivers and interactions of shelf waters with underlying sediments. Arctic rivers have much higher Hf concentrations (7-30 pM) than Arctic seawater (0.36-4.2 pM). Water from the Mackenzie River has the least radiogenic Hf, with εHf = -7.1 ± 1.7, and plots furthest away from the ferromanganese crust array, while waters from the Ob, Yenisey, and Lena Rivers have values that are indistinguishable from most Arctic rivers. In the Amundsen, Makarov, and Canada basins, Hf concentrations are highest at the surface and lowest in the deeper waters, reflecting the influences of riverine inputs and of waters that have flowed over the extensive Siberian continental shelves and have Nd and Hf characteristics that reflect water-sediment interactions. This is in contrast to the relatively low near surface Hf concentrations reported for locations elsewhere. The Pacific water layer in the Canada basin exhibits the highest values of εHf = + 6.8 ± 1.8, relecting the Hf isotopic composition of waters entering the Arctic from the Pacific Ocean. Mixing relationships indicate that a substantial fraction of the Hf in the Mackenzie River is lost during estuarine mixing; the behaviour of Hf from other rivers is less constrained.